2021
DOI: 10.1155/2021/5245621
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Performance of Ratio-Exponential-Log Type General Class of Estimators Using Two Auxiliary Variables

Abstract: In this paper, a ratio-exponential-log type general class of estimators is proposed in estimating the finite population mean using two auxiliary variables when population parameters of the auxiliary variables are known. From the proposed estimator, some special estimators are identified as members of the proposed general class of estimators. The mean square error (MSE) expressions are obtained up to the first order of approximation. This study finds that the proposed general class of estimators outperforms as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…By employing simple random sampling without replacement, 25 samples of size 5 are drawn from the population at regular intervals, and the results are compiled in Table 7. Each sample provides the usual mean estimators as ȳ and x, while the classical ratio estimator r , logarithmic estimator a , memory-type ratio estimator m r , and MTLE m a are computed using (1), ( 7), (12), and (18). Each sample is used to construct the EWMA statistic with η = 0.25.…”
Section: Numerical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…By employing simple random sampling without replacement, 25 samples of size 5 are drawn from the population at regular intervals, and the results are compiled in Table 7. Each sample provides the usual mean estimators as ȳ and x, while the classical ratio estimator r , logarithmic estimator a , memory-type ratio estimator m r , and MTLE m a are computed using (1), ( 7), (12), and (18). Each sample is used to construct the EWMA statistic with η = 0.25.…”
Section: Numerical Studymentioning
confidence: 99%
“…Ref. [12] measured the effectiveness of the ratio-exponential-log type general class of estimators by utilizing two auxiliary variables. Logarithmic-type predictive estimators for population mean based on an RSS scheme were studied by [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is very popular when auxiliary information is considered at the estimation phase, the ratio, product, regression, and exponential type estimators are mostly the preferred methods in di erent dimensions. Shabbir et al [1] examined the performance of ratio-exponential log type class of estimators using two auxiliary variables. Shahzad et al [2] introduced a novel family of variance estimators based on L-moments and calibration approach under strati ed simple random sampling (SSRS), whereas Shahzad et al [3] suggested L-Moments and calibration-based variance estimators under double SSRS and discussed an application of COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%